Improving soil organic carbon pools through inclusion of summer mungbean in cereal-cereal cropping systems in Indo-Gangetic plain. Issue 12 (15th October 2018) - Hazra, Kali Krishna; Ghosh, Probir Kumar; Venkatesh, Madasur Subbabhat; Nath, Chaitanya Prasad; Kumar, Narendra; Singh, Mohan; Singh, Jagdish; Nadarajan, Nagasamy
ABSTRACT: Long-term effect of mungbean inclusion in lowland rice-wheat and upland maize-wheat systems on soil carbon (C) pools, particulate organic C (POC), and C-stabilization was envisaged in organic, inorganic and without nutrient management practices. In both lowland and upland systems, mungbean inclusion increased very-labile C (C frac 1 ) and labile C (C frac 2 ) in surface soil (0–0.2 m). Mungbean inclusion in cereal-cereal cropping systems improved POC, being higher in lowland (107.4%). Lowland rice-based system had higher passive C-pool (11.1 Mg C ha −1 ) over upland maize-based system (6.6 Mg C ha −1 ) indicating that rice ecology facilitates the stabilization of passive C-pool, which has longer persistence in soil. Organic nutrient management (farmyard manure + full crop residue + biofertilizers) increased C frac 1 and carbon management index (CMI) over inorganic treatment. In surface soil, higher CMI values were evident in mungbean included cropping systems in both lowland and upland conditions. Mungbean inclusion increased grain yield of cereal crops, and yield improvement followed the order of maize (23.7–31.3%) > rice (16.9–27.0%) > wheat (lowland 7.0–10.7%; upland 5.4–16.6%). Thus, the inclusion of summer mungbean in cereal-cereal cropping systems could be a long-term strategy to enrich soil organic C and to ensure sustainability of cereal-cereal cropping systems.